A new affinity reagent for the site-specific, covalent attachment of DNA to active-site nucleophiles: application to the EcoRI and RsrI restriction and modification enzymes. - Purmal, A A (1992)
A modified oligodeoxyribonucleotide duplex containing an unnatural internucleotide trisubstituted 3' to 5' pyrophosphate bond in one strand [5'(oligo1)3'-P(OCH3)P-5'(oligo2) 3'] reacts with nucleophiles in aqueous media by acting as a phosphorylating affinity reagent. When interacted with a protein, a portion of the oligonucleotide [--P-5'(oligo2)3'] becomes attached to an amino acid nucleophilic group through a phosphate of the O-methyl-modified pyrophosphate linkage. We demonstrate the affinity labeling of nucleophilic groups at the active sites of the EcoRI and RsrI restriction and modification enzymes with an oligodeoxyribonucleotide duplex containing a modified scissile bond in the EcoRI recognition site. With the EcoRI and RsrI endonucleases in molar excess approximately 1% of the oligonucleotide becomes attached to the protein, and with the companion methyltransferases the yield approaches 40% for the EcoRI enzyme and 30% for the RsrI methyltransferase. Crosslinking proceeds only upon formation of a sequence-specific enzyme-DNA complex, and generates a covalent bond between the 3'-phosphate of the modified pyrophosphate in the substrate and a nucleophilic group at the active site of the enzyme. The reaction results in the elimination of an oligodeoxyribonucleotide remnant that contains the 3'-O-methylphosphate [5'(oligo1)3'-P(OCH3)] derived from the modified phosphate of the pyrophosphate linkage. Hydrolysis properties of the covalent protein-DNA adducts indicate that phosphoamide (P-N) bonds are formed with the EcoRI endonuclease and methyltransferase.